Exploring Local Potency of Purbalingga Regency to Improve Creative Thinking Skill of Elementary School Students (Universitas Negeri Semarang, 2019)
The observation results at 27 elementary school students indicate that the learning process did not yet support the development of students' creative thinking abilities. Students who recognize cultural diversity will tend to have creative thinking ability. Unfortunately, culture utilization as a source of learning in the school was not optimal, so students were less familiar with the culture in their area. But, creative thinking through learning Project-based Learning (PjBL) model by using local wisdom resource will help students to improve their abilities. This study aims to determine the application of PjBL with science aspects related to community culture (ethnoscience) and the creative thinking abilities improvement of elementary school students. This experimental research design used a pre-test and post-test design control group. The research sample consisted of students fifth-graders Public Elementary School 2 Majasari and Public Elementary School 3 Majasari. Data collection used observation techniques, written tests, questionnaires, and documentation. The positive findings in the normalized gain test analysis of the experimental class and the control class showed a moderate increase of 0.4 and 0.3. The increase in students' creative thinking abilities in the experimental class was higher than in the control class. The results of the study concluded that the application of ethnoscience based PjBL could improve students' creative thinking abilities.